An artificial intelligence-based approach for identifying rare disease patients using retrospective electronic health records applied for Pompe disease - Lin, Simon; Nateqi, Jama; Weingartner-Ortner, Rafael; Gruarin, Stefanie; Marling, Hannes; Pilgram, Vinzenz; Lagler, Florian B.; Aigner, Elmar; Martin, Alistair G. (Frontiers in Neurology, 2023)
Objective: We retrospectively screened 350,116 electronic health records (EHRs) to identify suspected patients for Pompe disease. Using these suspected patients, we then describe their phenotypical characteristics and estimate the prevalence in the respective population covered by the EHRs. Methods: We applied Symptoma’s Artificial Intelligence-based approach for identifying rare disease patients to retrospective anonymized EHRs provided by the “University Hospital Salzburg” clinic group. Within one month, the AI screened 350,116 EHRs reaching back 15 years from five hospitals, and 104 patients were flagged as probable for Pompe disease. Flagged patients were manually reviewed and assessed by generalist and specialist physicians for their likelihood for Pompe disease, from which the performance of the algorithms was evaluated. Results: Of the 104 patients flagged by the algorithms, generalist physicians found 5 “diagnosed”, 10 “suspected”, and 7 patients with “reduced suspicion”. After feedback from Pompe disease specialist physicians, 19 patients remained clinically plausible for Pompe disease, resulting in a specificity of 18.27% for the AI. Estimating from the remaining plausible patients, the prevalence of Pompe disease for the greater Salzburg region (incl. Bavaria (Germany), Styria (Austria), and Upper Austria (Austria)) was 1 in every 18,427 people. Phenotypes for patient cohorts with an approximated onset of symptoms above or below one year of age were established, which correspond to infantile-onset Pompe disease (IOPD) and late-onset Pompe disease (LOPD), respectively. Conclusion: Our study shows the feasibility of Symptoma’s AI-based approach for identifying rare disease patients using retrospective EHRs. Via the algorithm’s screening of an entire EHR population, a physician had only to manually review 5.47 patients on average to find one suspected candidate. This efficiency is crucial as Pompe disease, while rare, is a progressively debilitating but treatable neuromuscular disease. As such, we demonstrated both the efficiency of the approach and the potential of a scalable solution to the systematic identification of rare disease patients. Thus, similar implementation of this methodology should be encouraged to improve care for all rare disease patients.